Web-Based Desktop Support Trouble Ticket System Design In PT. Mnc Mediacom Cable - Shulton, Besus Maulana; Zuraidah, Eva (Sinkron : jurnal dan penelitian teknik informatika, 2020)
In recent years the existence of web-based information systems in Indonesia has increasingly felt its presence in supporting daily activities, both economic and non-economic. Manually processing data certainly cannot keep up with the need for fast, precise, and accurate presentation of information. Currently, manual data processing is considered less effective for providing reports and information for companies that are developing and have diverse transactions. The importance of Trouble Ticket Desktop Support is to make equalization of workloads that are fair and balanced besides that it is also a tool for assessment on each a technician. So with this, the author tries to examine the application of web-based technology that can be applied to problems that exist in one activity so that it can integrate the activities concerned. Ticket Desktop Support as a process to collect data from various existing sources and Desktop Support is required to be active monitor and treat user needs. With Trouble Ticket Desktop Support that is well integrated so that accessing data on Desktop Support can be done easily and quickly in order to measure the level of problems and access reports by the Head of IT Operations, as well as problems can be handled well within the scope of problem boundaries that produce the right solution to manage resources the power available, with this application it will be clear what problems are faced by the customer.